Functional analysis of six Kir6.2 (KCNJ11) mutations causing neonatal diabetes. - Girard, C; Shimomura, K; Proks, P; Absalom, N; Castano, L; Perez de Nanclares, G; Ashcroft, F (2006)
ATP-sensitive potassium (K(ATP)) channels, composed of pore-forming Kir6.2 and regulatory sulphonylurea receptor (SUR) subunits, play an essential role in insulin secretion from pancreatic beta cells. Binding of ATP to Kir6.2 inhibits, whereas interaction of Mg-nucleotides with SUR, activates the channel. Heterozygous activating mutations in Kir6.2 (KCNJ11) are a common cause of neonatal diabetes (ND). We assessed the functional effects of six novel Kir6.2 mutations associated with ND: H46Y, N48D, E227K, E229K, E292G, and V252A. K(ATP) channels were expressed in Xenopus oocytes and the heterozygous state was simulated by coexpression of wild-type and mutant Kir6.2 with SUR1 (the beta cell type of SUR). All mutations reduced the sensitivity of the K(ATP) channel to inhibition by MgATP, and enhanced whole-cell K(ATP) currents. Two mutations (E227K, E229K) also enhanced the intrinsic open probability of the channel, thereby indirectly reducing the channel ATP sensitivity. The other four mutations lie close to the predicted ATP-binding site and thus may affect ATP binding. In pancreatic beta cells, an increase in the K(ATP) current is expected to reduce insulin secretion and thereby cause diabetes. None of the mutations substantially affected the sensitivity of the channel to inhibition by the sulphonylurea tolbutamide, suggesting patients carrying these mutations may respond to these drugs.